ChemInform Abstract: Organic Stereochemistry. Part 7. The Concept of Substrate Stereoselectivity in Biochemistry and Xenobiotic Metabolism. Issue 40 (12th September 2013) - Testa, Bernard
Abstract Review: 103 refs.